2012
DOI: 10.1113/jphysiol.2012.241281
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress contributes to the augmented exercise pressor reflex in peripheral arterial disease patients

Abstract: Key points• Peripheral arterial disease (PAD) is a common and debilitating condition linked with heightened risk of cardiovascular mortality.• Dynamic exercise elicits augmented blood pressure responses in PAD that could put the patient at risk for adverse event but the underlying mechanisms are unknown.• The exercise pressor reflex is comprised of group III and group IV muscle afferents that increase their discharge in response to mechanical and/or chemical stimulation.• In this study, we demonstrate that mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
105
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 53 publications
12
105
0
1
Order By: Relevance
“…After a 15-min quiet rest period, baseline BPs were obtained via automated oscillometry of the brachial artery (Philips SureSigns Vs3), and a blood sample was obtained for the measurement of thromboxane B 2 (stable marker of thromboxane A2) and 6-keto-PGF1␣ (stable marker of prostacyclin, Penn State Core Endocrine Laboratory, Hershey, PA). The calf of the supine volunteer was supported by cushions to assure a full range of motion (i.e., active plantar flexion), and a custom sandal was affixed to the foot, consistent with previous studies in our laboratory (13,28).…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…After a 15-min quiet rest period, baseline BPs were obtained via automated oscillometry of the brachial artery (Philips SureSigns Vs3), and a blood sample was obtained for the measurement of thromboxane B 2 (stable marker of thromboxane A2) and 6-keto-PGF1␣ (stable marker of prostacyclin, Penn State Core Endocrine Laboratory, Hershey, PA). The calf of the supine volunteer was supported by cushions to assure a full range of motion (i.e., active plantar flexion), and a custom sandal was affixed to the foot, consistent with previous studies in our laboratory (13,28).…”
Section: Methodsmentioning
confidence: 67%
“…In recent years, our laboratory has focused on BP control in patients with PAD. Specifically, we found that 1) the BP response to single-leg dynamic plantar flexion exercise was augmented in PAD patients compared with healthy control subjects; 2) the pressor response occurred at very low workloads and before the onset of pain; 3) the pressor response correlated with the anklebrachial index (ABI), suggesting that disease severity plays a role; and 4) intravenous infusion of ascorbic acid lowered the pressor response to exercise in PAD (13,28). To date, the mechanisms for these findings are largely unknown.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This reflex is activated when mechanical and metabolic signals originating within contracting skeletal muscles stimulate thinly myelinated group III and unmyelinated group IV muscle afferents (34,36,44). The exercise pressor reflex is exaggerated in patients with atherosclerotic peripheral artery disease (PAD; 31,39,40) which contributes to the larger increase in blood pressure found during treadmill walking in this patient population compared to that found in aged-matched healthy controls (5, 7). The exercise pressor reflex is also exaggerated in a rat model of simulated PAD in which a femoral artery is ligated ~24-72 hours before the experiment (51).…”
Section: Chapter 1 -Introductionmentioning
confidence: 91%
“…Improving limb blood flow, and possibly oxygen delivery, has the potential to attenuate the rate of development of peripheral muscle fatigue (3). Interestingly, intravenous AO administration also ameliorated the exaggerated exercise pressor reflex during plantar flexion exercise in patients with peripheral artery disease, which was attributed to a reduction in excessive group III/IV afferent stimulation under basal conditions (27). Decreasing the group III/IV afferent signal from the lower limbs has also been documented to extend exercise time to exhaustion in patients with COPD (17).…”
mentioning
confidence: 99%